2022
DOI: 10.1371/journal.pone.0275016
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of novel biomarkers for lupus nephritis—An overview of systematic reviews

Abstract: Introduction Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multiorgan inflammatory involvement and a mortality rate that is 2.6-fold higher than individuals of the same age and sex in the general population. Approximately 50% of patients with SLE develop renal impairment (lupus nephritis). Delayed diagnosis of lupus nephritis is associated with a higher risk of progression to end-stage renal disease, the need for replacement therapy, and mortality. The initial clinical manifestations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 129 publications
0
12
0
Order By: Relevance
“…All these urinary cell membrane biomarkers can be used to monitor the treatment response and flares [125], and at baseline, the NGAL levels best predict, as compared to VCAM and KIM1, responders from non-responders 6 months after the induction phase with an AUC = 0.78 [37]. ROC and/or Cox regression analysis further showed that persistently high urinary VCAM1, NGAL, KIM1, and sCD163 levels can predict ESKD evolution [37,116,125,126]. The added value to combine these markers needs to be further evaluated.…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…All these urinary cell membrane biomarkers can be used to monitor the treatment response and flares [125], and at baseline, the NGAL levels best predict, as compared to VCAM and KIM1, responders from non-responders 6 months after the induction phase with an AUC = 0.78 [37]. ROC and/or Cox regression analysis further showed that persistently high urinary VCAM1, NGAL, KIM1, and sCD163 levels can predict ESKD evolution [37,116,125,126]. The added value to combine these markers needs to be further evaluated.…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
“…The top five urinary cytokines/chemokines evaluated in LN included: tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK); monocyte chemoattractant protein-1 (MCP-1/CCL2); IFN inducible protein-10 (IP-10/CXCL10); B-cell-activating factor of the tumor necrosis factor family (BAFF/BLySS); and proliferation-inducing ligand (APRIL) [114,115]. Among them, biomarkers with a good/very good AUC for predicting LN included urinary MCP-1/CCL2 (AUC = 0.90) > BAFF (AUC = 0.825) = TWEAK (AUC = 0.82) > IP-10 (0.6 < AUC < 1.0) [116,117]. When combined, urinary MCP-1/CCL2 and TWEAK are effective in discriminating between an active and inactive LN (AUC = 0.89), and ESKD evolution (AUC = 0.78).…”
Section: Cytokines/chemokinesmentioning
confidence: 99%
“…For instance, B-cell activating factor (BAFF or BLyS), produced by glomerular macrophages and mesangial cells, stimulates B-cell activation both directly and by inducing the production of pro-inflammatory molecules, such as IFN-α, perpetuating a detrimental cycle in the renal microenvironment. Moreover, cytokines, such as urinary monocyte chemoattractant protein-1 (MCP-1/CCL2), BAFF, and TNF-related weak inducer of apoptosis (TWEAK), are pertinent in predicting active LN, assessing therapeutic responses, and forecasting disease flares [53,54].…”
Section: Cytokines/chemokinesmentioning
confidence: 99%
“…In an overview of systematic reviews by Guimaraes et al, the biomarkers with the best accuracy profile were urinary tumor necrosis factor-like weak inducer of apoptosis (uTWEAK), a member of the TNF superfamily, urinary monocyte chemoattractant protein-1 (uMCP-1), and urinary neutrophil gelatinase-associated lipocalin (uNGAL), which were more sensitive than specific for most of the analyzed outcomes [ 111 ]. SLE patients with active kidney disease have significantly higher urinary TWEAK levels than SLE patients without active kidney disease [ 112 ].…”
Section: Biomarkers Of Glomerular Diseasesmentioning
confidence: 99%